PENGARUH FAMA-FRENCH FIVE FACTOR MODEL TERHADAP RETURN SAHAM - Dewanto, Cliff; Sumiati, Sumiati (Jurnal Management Risiko dan Keuangan, 2022)
Estimating the risk and return of a stock is important for an investor. The Fama and French is a model to predict and identify the tradeoff of purchased shares. Infrastructure is one of the sectors in the Indonesia Stock Exchange that experienced significant declines. The objective of this explanatory research is to identify the effect of Fama-French Model usage on stock return. The population are all 57 infrastructure-sector companies listed on the Indonesia Stock Exchange from December 2015 to December 2019. Using purposive sampling technique, thirty companies were selected as the sample. The results of the multiple linear regression analysis show that market excess return, book-to-market (HML), profitability (RMW), and investment pattern (CMA) have a positive and significant effect on stock returns and that size (SMB) negatively and significantly influences stock returns.